PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING (SFAE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KIMIA KOLOID DI KELAS XI IPA SMA SANTA MARIA PEKANBARU - Heru Christianto; Johni Azmi; Susilawati Susilawati (Pascasarjana Universitas Negeri Medan, 2014)
Abstract. The Research is about using cooperative learning model of Student Facilitator and Explaining (SFAE) type which has been done to know improvement student’s achievement on the topic of colloid at XIIPA classes of SMA Saint Marie Pekanbaru in the second semester of academic year 2012/2013. This research is experimental research based on pretest-posttest design. The sample consisted of two classes, XI IPA2 class as experiment group and XI IPA3 class as control group that randomly selected after testing homogeneity. Cooperative learning model of Student Facilitator and Explaining (SFAE) type is applied in XI IPA2. Analysis of data used t-test. Results of data processing obtained tcount > ttable (2,28 > 1,67). It means that using cooperative learning model of Student Facilitator and Explaining (SFAE) type can improve student’s achievement on the topic of colloid at XI IPA classes of SMA Saint Marie Pekanbaru. The improvement of student’s achievement in experiment class was supported by N-Gain score as many as 0,78 that included in high category. Keyword : Cooperative Learning of Student Facilitator and Explaining, Student’s Achievement, Colloid